Autophagy in light-induced retinal damage. (March 2016) - Chen, Yu; Perusek, Lindsay; Maeda, Akiko
Abstract: Vision is reliant upon converting photon signals to electrical information which is interpreted by the brain and therefore allowing us to receive information about our surroundings. However, when exposed to excessive light, photoreceptors and other types of cells in the retina can undergo light-induced cell death, termed light-induced retinal damage. In this review, we summarize our current knowledge regarding molecular events in the retina after excessive light exposure and mechanisms of light-induced retinal damage. We also introduce works which investigate potential roles of autophagy, an essential cellular mechanism required for maintaining homeostasis under stress conditions, in the illuminated retina and animal models of light-induced retinal damage. Highlights: Excessive exposure to light can cause light-induced retinal damage. Complex mechanisms involving autophagy have been reported in light-induced retinal damage. Defects in essential molecules for autophagy can modulate the severity of light-induced damage. Autophagy could play an important role in coping with stress during the perception of light in the retina.